Low-Concentration Atropine for Myopia Progression (LAMP) Study: A Randomized, Double-Blinded, Placebo-Controlled Trial of 0.05%, 0.025%, and 0.01% Atropine Eye Drops in Myopia Control - Yam, Jason C; Jiang, Yuning; Tang, Shu Min; Law, Antony K P; Chan, Joyce J; Wong, Emily; Ko, Simon T; Young, Alvin L; Tham, Clement C; Chen, Li Jia; Pang, Chi Pui (Ophthalmology (Rochester, Minn.), 2019)
Low-concentration atropine is an emerging therapy for myopia progression, but its efficacy and optimal concentration remain uncertain. Our study aimed to evaluate the efficacy and safety of low-concentration atropine eye drops at 0.05%, 0.025%, and 0.01% compared with placebo over a 1-year period. Randomized, placebo-controlled, double-masked trial. A total of 438 children aged 4 to 12 years with myopia of at least -1.0 diopter (D) and astigmatism of -2.5 D or less. Participants were randomly assigned in a 1:1:1:1 ratio to receive 0.05%, 0.025%, and 0.01% atropine eye drops, or placebo eye drop, respectively, once nightly to both eyes for 1 year. Cycloplegic refraction, axial length (AL), accommodation amplitude, pupil diameter, and best-corrected visual acuity were measured at baseline, 2 weeks, 4 months, 8 months, and 12 months. Visual Function Questionnaire was administered at the 1-year visit. Changes in spherical equivalent (SE) and AL were measured, and their differences among groups were compared using generalized estimating equation. After 1 year, the mean SE change was -0.27±0.61 D, -0.46±0.45 D, -0.59±0.61 D, and -0.81±0.53 D in the 0.05%, 0.025%, and 0.01% atropine groups, and placebo groups, respectively (P < 0.001), with a respective mean increase in AL of 0.20±0.25 mm, 0.29±0.20 mm, 0.36±0.29 mm, and 0.41±0.22 mm (P < 0.001). The accommodation amplitude was reduced by 1.98±2.82 D, 1.61±2.61 D, 0.26±3.04 D, and 0.32±2.91 D, respectively (P < 0.001). The pupil sizes under photopic and mesopic conditions were increased respectively by 1.03±1.02 mm and 0.58±0.63 mm in the 0.05% atropine group, 0.76±0.90 mm and 0.43±0.61 mm in the 0.025% atropine group, 0.49±0.80 mm and 0.23±0.46 mm in the 0.01% atropine group, and 0.13±1.07 mm and 0.02±0.55 mm in the placebo group (P < 0.001). Visual acuity and vision-related quality of life were not affected in each group. The 0.05%, 0.025%, and 0.01% atropine eye drops reduced myopia progression along a concentration-dependent response. All concentrations were well tolerated without an adverse effect on vision-related quality of life. Of the 3 concentrations used, 0.05% atropine was most effective in controlling SE progression and AL elongation over a period of 1 year.